All new Decoupage : Over 20 Practical and Inspirational Projects - Morbin, Deborah & Boomer, Tracy (UK A David & Charles Book, 2004)
Traditional decoupage has moved on, and this book features the latest developments in the craft, with a number of interesting and innovative variations involving more traditional techniques. Packed with imaginative ideas and tricks of the trade All New Decoupage provides everything you need to know to create attractive and elegant items decoupaged to suit the stylish simplicity of the 21st century.
Include Colour Illustrations
Keywords: Decoupage -- Handicraft